The Extract Standardization Test and Physical Properties Evaluation of Uncaria gambier Roxb Extract Catechine Capsules - Oktavilantika, Dina Melia; Suzana, Dona; Himawati, Ditiya; Putra, Hendri Dwi (Faculty of Pharmacy, Universitas Muslim Indonesia, 2024)
Society does not really know that the catechin extract contained in uncaria gambir roxb can be used as an anti-inflammatory and antioxidant. The catechins in gambier plant are very complex. They are composed of extracts of catechins (C), epicatechins (EC), epicatechin gallate (ECG), epigalocatechin (EGC), epigalocatechin gallate (EGCG), and galocatechin (GC). Thus, the use of this medicinal plants with anti-inflammatory and antioxidant properties needs to be developed as an alternative treatment. In addition, this species of plant has also important effectiveness and relatively smaller side effects. In an effort to increase efficiency and maximize the therapeutic effects of gambier as an anti-inflammatory and antioxidant, the authors need to develop an innovate pharmaceutical product from this plant. One of the selected pharmaceutical preparations is the capsule since it can conceal the taste and the unpleasant smell; besides, it is also easy to consume. The maceration method was carried out in the catechin extraction process. After obtaining pure catechin extracts, the authors tested catechin levels using the HPLC method and antioxidant levels using the DPPH method. Next, the authors performed extract standardization tests, and evaluated the physical properties of the capsule preparations. The test results showed catechin levels of 98.697% and IC50 antioxidant levels of 8.54 µg/dl. The results of the standardized extract and capsule evaluation tests indicated that they met the applicable requirements.